Preventive Maintenance Scheduling by Mathematical Programming - Wagner, Harvey M.; Giglio, Richard J.; Glaser, R. George (Management Science, 1964)
This paper explores methods for scheduling preventive maintenance by means of mathematical programming. Five integer linear programming models are posed, each based on a different optimality criterion dealing with manpower smoothing. By means of two hypothetical examples the models are tested for their computational properties. In addition to describing the experimental results of applying integer linear programming techniques to this class of problems, the paper also illustrates how effectively rounded linear programming solutions can be used as approximations to optimal solutions.